2004
DOI: 10.1063/1.1804153
|View full text |Cite
|
Sign up to set email alerts
|

Ionization and solvation of HCl adsorbed on the D2O-ice surface

Abstract: The interaction of HCl with the D(2)O-ice surface has been investigated in the temperature range 15-200 K by utilizing time-of-flight secondary ion mass spectroscopy, temperature-programmed desorption, and x-ray photoelectron spectroscopy. The intensities of sputtered H(+)(D(2)O) and Cl(-) ions (the H(+) ions) are increased (decreased) markedly above 40 K due to the hydrogen bond formation between the HCl and D(2)O molecules. The HCl molecules which form ionic hydrates undergo H/D exchange at 110-140 K and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…To date, TP-TOF-SIMS has revealed that both HCl and NH 3 molecules adsorbed on pure ASW films are hydrated considerably up to 140 K [22][23][24], which is consistent with the conclusions drawn using different approaches [3][4][5][6]8,9,13,14]. However, very little is known about intermolecular interactions at the surface of acidic and basic water-ice films including hydrated HCl or NH 3 molecules, respectively.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…To date, TP-TOF-SIMS has revealed that both HCl and NH 3 molecules adsorbed on pure ASW films are hydrated considerably up to 140 K [22][23][24], which is consistent with the conclusions drawn using different approaches [3][4][5][6]8,9,13,14]. However, very little is known about intermolecular interactions at the surface of acidic and basic water-ice films including hydrated HCl or NH 3 molecules, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…NH þ 4 þCl À ðH 2 OÞ n ). The latter is more likely, as inferred from our results [23] showing that neutral HCl molecules are incorporated into the bulk while ionic hydrates [i.e., (H 3 O) + Cl À (H 2 O) nÀ1 ] stay at the surface or in subsurface sites. In any case, the direct contact between NH 3 and HCl or Cl À is prerequisite for the increase in NH þ 4 intensity.…”
Section: Nh 3 On Acidic Water-ice Filmmentioning
confidence: 53%
See 2 more Smart Citations
“…In matrix isolation spectroscopy such a transition was claimed, although the assignment of the bands to the correct size is difficult [53]. The HX dissociation has been theoretically studied on model ice surfaces [57][58][59][60][61][62], and it has also been the subject of extensive experimental investigations using temperature controlled desorption, X-ray absorption spectroscopy, reactive Cs þ ion scattering, low energy sputtering and Fouriertransform infrared spectroscopy [63][64][65][66][67][68][69][70][71]. On the other hand, vibrational spectroscopy of free HCl(H 2 O) n clusters could only unambiguously identify covalently bound species up to n ¼ 2 [55,56].…”
Section: Photoinduced Processes Of Hydrogen Halides In Watermentioning
confidence: 99%